Teaching Japanese at Jagiellonian University – Prospects for Philology? - Huszcza, Romuald (Acta Orientalia Vilnensia, 2005)
Jagiellonian University, CracowIn the present paper, I would like to discuss some important aspects of the status of Japanese studies at the Jagiellonian University, the main topic of discussion being the present state and future prospects of this field, i.e. of both language teaching and academic research in a region which has recently been labeled “EU new member countries”.